EUROPEJSKA KONWENCJA O PRZYSPOSOBIENIU DZIECI JAKO INSTRUMENT WSPÓLNYCH ZASAD PAŃSTW CZŁONKOWSKICH RADY EUROPY W SPRAWACH O PRZYSPOSOBIENIE DZIECI - Morawska, Elżbieta Hanna (Zeszyty Prawnicze, 2016)
The European Convention on the Adoption of Children as an Instrument of the Common Principles of the Member States of the Council of Europe on the Adoption of Children Summary Acting on the grounds of its statutory aims, the Council of Europe has taken a number of measures for the protection and promotion of children’s rights. The nature of these activities has differed considerably in the course of over 60 years since the Council’s establishment, nonetheless all of them have invoked children’s welfare as the basis of their undertaking. This is the spirit in which already in the early 1950s the Council embarked on an effort to draw up a European convention on the adoption of children. The Convention was the first treaty regulating the procedure for adoption in a comprehensive manner, and as such paved the way for subsequent European documents relating to the rights and protection of children, also in the adoption process. The collection of these documents includes detailed conventions specifically on the protection of children, alongside documents which do not directly address children’s rights and protection, but apply to the protection of human rights in general under the Council of Europe system. The principal document is the European Convention on Human Rights, along with its additional protocols, in particular Protocol 7. The approach to adoption based on the European Convention on Human Rights led the Council of Europe to embark on a new project to define the principles and practices for adoption. The outcome of this work is the Revised European Convention on the Adoption of Children (RECAC, 2007), the document containing the definitions of currently applicable principles and practices.